Systematic assessment of BDNF and its receptor levels in human cortices affected by Huntington's disease - Zuccato, Chiara; Marullo, Manuela; Conforti, Paola; MacDonald, Marcy E; Tartari, Marzia; Cattaneo, Elena (Brain pathology (Zurich, Switzerland), 2008)
One cardinal feature of Huntington's disease (HD) is the degeneration of striatal neurons, whose survival greatly depends on the binding of cortical brain-derived neurotrophic factor (BDNF) with high-affinity (TrkB) and low-affinity neurotrophin receptors [p75 pan-neurotrophin receptor (p75(NTR))]. With a few exceptions, results obtained in HD mouse models demonstrate a reduction in cortical BDNF mRNA and protein, although autopsy data from a limited number of human HD cortices are conflicting. These studies indicate the presence of defects in cortical BDNF gene transcription and transport to striatum. We provide new evidence indicating a significant reduction in BDNF mRNA and protein in the cortex of 20 HD subjects in comparison with 17 controls, which supports the hypothesis of impaired BDNF production in human HD cortex. Analyses of the BDNF isoforms show that transcription from BDNF promoter II and IV is down-regulated in human HD cortex from an early symptomatic stage. We also found that TrkB mRNA levels are reduced in caudate tissue but not in the cortex, whereas the mRNA levels of T-Shc (a truncated TrkB isoform) and p75(NTR) are increased in the caudate. This indicates that, in addition to the reduction in BDNF mRNA, there is also unbalanced neurotrophic receptor signaling in HD.